The Influence of Motivation and Work Environment on Employee Performance at PT. Sumber Data Indonesia South Jakarta - Astria, Kenny (International Journal of Business and Applied Economics, 2025)
This research investigates the outcomes of motivation and work environment on employee performance at PT Sumber Data Indonesia in South Jakarta. A quantitative approach was employed, utilising the Slovin formula for sampling, which yielded a sample size of 86 individuals. The data analysis encompassed validity testing, reliability assessment, classical hypothesis testing, regression analysis, correlation coefficients, coefficients of determination, and hypothesis evaluation. The study's results indicated that motivation had a considerable impact on employee performance, evidenced by a coefficient of determination of 49.2%. The hypothesis testing demonstrated that the t-statistic surpassed the crucial t-value (9.019 > 1.989).